The Interpretation of Metamorphosis as a Narrative Device in George MacDonald’s Fairy Tales - Hayroyan, Diana (Armenian Folia Anglistika, 2014)
The following article is an attempt to study metamorphosis as a narrative device in Scottish fairy tale writer George MacDonald’s fairy tales. Due to a closer study of the theoretical background of metamorphosis and the analyses of the examples it becomes possible to describe metamorphosis not only as a stylistic but also as a narrative device. In the mentioned fairy tales metamorphosis, granting specific meaning to the events, reveals the unique poetics of the fairy tales and promotes a deeper understanding of the fairy tale text thus fulfilling the author’s intention.
Keywords: interpretation; fairy tale; metamorphosis; narrative device; trope